Evaluation of growth of young coconut and nut yield of old coconut and their nutrient status under coconut-cassava intercropping systems (Journal of Science and Technology, 2016)
Two on-farm experiments were carried out in the coconut belt of Southern Ghana from 2006 to 2009 to evaluate growth of young coconut plantings and nut yield of old coconut fields and their nutrient status under coconut-cassava intercropping systems. Experiment I was carried out inyoung MYD x VTT coconut plantings. Experiment II was conducted in old West African Tall coconut plantings. The same cropping systems were evaluated under the two experiments in randomized complete block design with two replications each. The cropping systems were: 1. Solecoconut 2. Coconut + non-fertilized cassava 3. Coconut + cassava-fertilizer-I (Fertilizer I= 30- 45-45 kg/ha N-P2O5-K2O) and 4. Coconut + cassava-fertilizer-II (Fertilizer II = 60-45-90 kg/ha N-P2O5-K2O). Young coconut planted as sole crop had significantly (p